Knowledge of the Nutritional and Medicinal Use of Some Vegetables among a Cross Section of Market Women in Two Major Food Markets in Lagos State, South West Nigeria - Awobajo, F.O.; Olatunji-Bello, I.I.; Obilade, T.T.; Odugbemi, T.O. (Pakistan Journal of Nutrition, 2010)
The knowledge of the nutritional and medicinal benefits of some vegetables found around the south west-Nigeria was tested among cross section of market women in Lagos state Nigeria, using questionnaires and coloured pictures of seventeen of these vegetables. This study was carried out in Lagos state which houses a cross section of the nation ethnic groups and also serves as the commercial nerve centre of Nigeria. One thousand market women with varying level of education were selected and tested on proper identification and their knowledge on nutritional and medicinal benefits of seventeen vegetables found around them. Sociodemographic data such as age, educational status were also recorded. The results revealed high percentage school dropout among the market women. There is also a level of ignorance about the available vegetables around among the market women thou there seems to be a good appreciation of their medicinal values. Considering the capital base of these women especially the largest age bracket of 21-45 years, we suggested that financially empowering them will reduce the vicious circle of poverty associated with school dropout among girls in Nigeria. The populace need to be educated about the readily available vegetables around them to reducing the incidence of macronutrient deficiencies.